Schizophrenia-related cognitive dysfunction in the Cyclin-D2 knockout mouse model of ventral hippocampal hyperactivity. Issue 1 (December 2018) - Grimm, Christina; Aksamaz, Sonat; Schulz, Stefanie; Teutsch, Jasper; Sicinski, Piotr; Liss, Birgit; Kätzel, Dennis
Abstract Elevated activity at the output stage of the anterior hippocampus has been described as a physiological endophenotype of schizophrenia, and its development maps onto the transition from the prodromal to the psychotic state. Interventions that halt the spreading glutamatergic over-activity in this region and thereby the development of overt schizophrenia could be promising therapies. However, animal models with high construct validity to support such pre-clinical development are scarce. The Cyclin-D2 knockout (CD2-KO) mouse model shows a hippocampal parvalbumin-interneuron dysfunction, and its pattern of hippocampal over-activity shares similarities with that seen in prodromal patients. Conducting a comprehensive phenotyping of CD2-KO mice, we found that they displayed novelty-induced hyperlocomotion (a rodent correlate of positive symptoms of schizophrenia), that was largely resistant against D1- and D2-dopamine-receptor antagonism, but responsive to the mGluR2/3-agonist LY379268. In the negative symptom domain, CD2-KO mice showed transiently reduced sucrose-preference (anhedonia), but enhanced interaction with novel mice and objects, as well as normal nest building and incentive motivation. Also, unconditioned anxiety, perseveration, and motor-impulsivity were unaltered. However, in the cognitive domain, CD2-knockouts showed reduced executive function in assays of rule-shift and rule-reversal learning, and also an impairment in working memory, that was resistant against LY379268-treatment. In contrast, sustained attention and forms of spatial and object-related memory that are mediated by short-term habituation of stimulus-specific attention were intact. Our results suggest that CD2-KO mice are a valuable model in translational research targeted at the pharmacoresistant cognitive symptom domain in causal relation to hippocampal over-activity in the prodrome-to-psychosis transition.